2017
DOI: 10.1186/s12885-017-3230-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of everolimus and metformin are complementary and glucose-dependent in breast cancer cells

Abstract: BackgroundClinical efficacy of the mTOR inhibitor everolimus is limited in breast cancer and regularly leads to side-effects including hyperglycemia. The AMPK inhibitor and anti-diabetic drug metformin may counteract everolimus-induced hyperglycemia, as well as enhancing anti-cancer efficacy. We investigated the glucose-dependent growth-inhibitory properties of everolimus, metformin and the combination in breast cancer cell lines.MethodsThe breast cancer cell lines MCF-7, MDA-MB-231 and T47D were cultured in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
5
28
1
Order By: Relevance
“…Limited availability of glucose and/or other nutrients increases the sensitivity of cancer cells to metformin [17,22,23,26,3139,46,47]. However, excepting glucose, the role of other nutrients and their combinations on the sensitivity of MDA-MB-231 cells to metformin was not examined in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited availability of glucose and/or other nutrients increases the sensitivity of cancer cells to metformin [17,22,23,26,3139,46,47]. However, excepting glucose, the role of other nutrients and their combinations on the sensitivity of MDA-MB-231 cells to metformin was not examined in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic pathways of cancer cells in vitro vary also between monolayer cultures and physiologically more relevant tumour spheroids [912]. Nutrient availability and metabolic phenotype can modify the sensitivity of cancer cells to pharmacological compounds that target cancer cell metabolism, such as metformin [17,22,23,26,3139,46,47]. Recently, we have shown that maintaining constant glucose concentrations by daily medium renewal blocks the effects of metformin on MDA-MB-231 cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 In breast cancer cells, cotreatment with metformin and everolimus intensified the inhibition of cell proliferation and colony formation. 44 Metformin and everolimus significantly suppressed obesity-induced tumor growth (0.5-fold and 0.3-fold). 45 It was also reported that the effect of everolimus might be associated with insulin resistance, manifesting in impaired glucose tolerance or hyperglycemia, whereas metformin could restore it.…”
Section: Combination Of Metformin With Everolimusmentioning
confidence: 95%
“…In breast cancer cells, cotreatment with metformin and everolimus intensified the inhibition of cell proliferation and colony formation . Metformin and everolimus significantly suppressed obesity‐induced tumor growth (0.5‐fold and 0.3‐fold) .…”
Section: Combination Of Metformin With Small Molecular Inhibitorsmentioning
confidence: 99%